Optimized Isolation of Protein Fractions from Brewer’s Spent Grain by Extraction with Ethanol and Mild Alkali - Kumar,P; Nakasu,PYS; Shmool,TA; Hallett,JP; Brandt-Talbot,A (ACS Sustainable Chemistry & Engineering, 2026)
Abstract Spent grain is the largest by-product of ethanol production from cereal grains. While spent grains can be used as livestock feed, fractionation could enable a wider range of applications. This study investigated multistep fractionation of an air-dried mixed Brewer’s Spent Grain (BSG) with 23% protein content from a small brewery to obtain protein concentrates, an organic solvent-soluble fraction, and a protein-depleted BSG residue. After screening of pre-extraction solvents (hot water, cyclohexane, ethanol, and water + ethanol), hot ethanol was selected followed by a three-step protein extraction with 0.1 M aqueous alkali at ambient temperature and by isoelectric precipitation at pH 3.5. The conditions yielded two protein products: an alkali-soluble protein precipitate (32% protein yield, 75% protein content) and an alkali-insoluble protein concentrate (18% protein yield, 44% protein content), which was separated from the protein-depleted residue based on density. The combined protein yield (up to 50%) exceeds previously reported yields for precipitated BSG protein products. Glucan analysis revealed that the protein products contained significant amounts of starch resistant to enzymatic hydrolysis. Comprehensive compositional analysis of the starting material, protein products, and residue enabled detailed mass balances. Although selective protein separation remains challenging due to coextraction of other biopolymers, the composition of the isolated protein concentrates supports potential valorization beyond livestock feed, including human nutrition and packaging materials. Identifying applications for the protein-depleted fraction remains important.